2008
DOI: 10.1007/s10653-008-9197-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination of paddy soils and rice (Oryza sativa L.) from Kočani Field (Macedonia)

Abstract: This research focuses on the heavy metal contamination of the paddy soils and rice from Kočani Field (eastern Macedonia) resulting from irrigation by riverine water impacted by past and present base-metal mining activities and acid mine drainage. Very high concentrations of As, Cd, Cu, Pb and Zn were found in the paddy soils (47.6, 6.4, 99, 983 and 1,245 lg g -1 ) and the rice (0.53, 0.31, 5.8, 0.5 and 67 lg g -1 ) in the western part of Kočani Field, close to the Zletovska River, which drains the mining facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 23 publications
1
25
2
Order By: Relevance
“…In their study, rice grains collected from CKDue endemic regions of Madawachchiya had the Cd content ranging from 0.001 to 0.093 mg/kg dry weight with a mean value 0.0444 mg/kg and Anuradhapura area had 0.001-0.194 mg/kg Cd, with a mean value of 0.0404 mg/kg. The Cd levels obtained in the present study are lower than those in rice grains collected near a base metal mining area in Macedonia (0.31 mg/kg) (Rogan et al 2008), raw rice grains from Sri Lanka (0.192 mg/kg) (Jayasekera and Freitas 2005), and rice collected from Lahore, Pakistan (0.23 mg/kg) (Hussain 1991), and the Codex Alimentatius Commission allowable limit (0.2 mg/kg) (Codex 2005). Table 6 shows the urinary cadmium concentration in CKDue patients, their immediate relatives and asymptomatic persons from Kandy, a non-endemic area in the central Sri Lanka.…”
Section: Environmental CD and Ckduecontrasting
confidence: 80%
See 1 more Smart Citation
“…In their study, rice grains collected from CKDue endemic regions of Madawachchiya had the Cd content ranging from 0.001 to 0.093 mg/kg dry weight with a mean value 0.0444 mg/kg and Anuradhapura area had 0.001-0.194 mg/kg Cd, with a mean value of 0.0404 mg/kg. The Cd levels obtained in the present study are lower than those in rice grains collected near a base metal mining area in Macedonia (0.31 mg/kg) (Rogan et al 2008), raw rice grains from Sri Lanka (0.192 mg/kg) (Jayasekera and Freitas 2005), and rice collected from Lahore, Pakistan (0.23 mg/kg) (Hussain 1991), and the Codex Alimentatius Commission allowable limit (0.2 mg/kg) (Codex 2005). Table 6 shows the urinary cadmium concentration in CKDue patients, their immediate relatives and asymptomatic persons from Kandy, a non-endemic area in the central Sri Lanka.…”
Section: Environmental CD and Ckduecontrasting
confidence: 80%
“…Table 6 shows the urinary cadmium concentration in CKDue patients, their immediate relatives and asymptomatic persons from Kandy, a non-endemic area in the central Sri Lanka. The results indicate relatively higher values of urinary Cd in CKDue patients compared to asymptomatic groups, but the values are several times lower in magnitude than the data given in Bandara et al (2008), in which the mean urinary cadmium concentration in CKDue b After Rogan et al (2008) c Jayasekera and Freitas (2005) d Hussain (1991) patients of age group 40-60 years was 7.58 lgCd/g creatinine and in asymptomatic persons it was 11.62 lgCd/g creatinine. WHO standards stipulate that a urinary excretion of 2 lgCd/g creatinine is normal, while 10 lgCd/g creatinine would indicate an irreversible situation of chronic exposure and potential renal dysfunction.…”
Section: Environmental CD and Ckduementioning
confidence: 56%
“…However, rice is also recognized as a major dietary source for metal(loid) exposure Williams et al 2009). Many studies, from various countries, have reported metal(loid) concentrations that exceed guidance values (Herawati et al 2000;Wang et al 2001;Cheng et al 2006b;Meharg et al 2009;Rogan et al 2009). The exposure to metal(loid)s through the consumption of contaminated rice brings elevated risk to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated Pb in soils may compromise soil productivity, and a very low Pb concentration may inhibit some vital plant processes, such as photosynthesis, mitosis, and water absorption, with toxic symptoms of dark green leaves, wilting of older leaves, stunted foliage and brown short roots (Kabata-Pendias and Pendias, 1992). Agricultural soils have a wide range of Pb content which depends on a number of factors, such as the parent material and the anthropogenic input (Rogan et al, 2009). Cd is considered as one of the most environmentally hazardous trace metals.…”
Section: Introductionmentioning
confidence: 99%